Integrating Health and Community Development for Health Equity: Philanthropic Investments in Baltimore City, 2010?2017 - Jessica L. Young; David J. Hawthorne (Mary Ann Liebert, 2019)
Purpose: Achieving health equity requires addressing the social determinants of health, which philanthropy has supported through community development grants. This study analyzes health topics that have been integrated into community development grants. Methods: Community development grants from 2010 to 2017 were analyzed for health topics in Baltimore, MD. Results: Food and nutrition, chronic disease, reproductive health, adolescent health, violence prevention, health care access, and infectious disease were the least common health topics in community development grants. Conclusion: To support health equity efforts, funders should consider a broader range of health issues to integrate into community development investments.